Comparison of trace elements concentrations in scalp hair of epileptic and normal subjects - Avci, H.; Kizilkan, N.; Yaman, M. (Dustri-Verlag Dr Karl Feistle, 2008)
Trace elements including Cu, Fe, Zn, Mg and Ca were determined in scalp hair of epileptic and healthy residents in Elazig, Turkey. The analyses were carried out by flame atomic absorption spectrometry (FAAS). To assess the best dissolution method, wet and microwave digestion procedures were examined. Various parameters that influence the sample preparation such as digestion time, kind of solvent and ratio of acid mixture were studied. The concentrations of Cu, Fe, Zn, Mg and Ca in scalp hair of 22 subjects with epilepsy were compared with those in 23 healthy control subjects. The hair of subjects with epilepsy showed significant lower levels of Cu and Fe for mate and female groups, and Mg for female group, when compared with control group. No differences were observed between the two groups for Zn concentrations. The mean levels of Ca in the hair of the epileptic group were quite close to the control group for both male and female subjects. The differences between control and those with epilepsy groups could be of particular interest for the investigation of the cause of epilepsy. Furthermore, it was found that the ratios of Cu/Fe for the epilepsy group were higher than for the normal group, at least 1.5-times. The results obtained were compared with corresponding data reported in the literature.
Keywords: epilepsy; scalp hair; trace elements; microwave digestion; flame atomic absorption spectrometry